# 6p-(5p+5)=-8-2(p+12)

## Simple and best practice solution for 6p-(5p+5)=-8-2(p+12) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for 6p-(5p+5)=-8-2(p+12) equation:

Simplifying
6p + -1(5p + 5) = -8 + -2(p + 12)

Reorder the terms:
6p + -1(5 + 5p) = -8 + -2(p + 12)
6p + (5 * -1 + 5p * -1) = -8 + -2(p + 12)
6p + (-5 + -5p) = -8 + -2(p + 12)

Reorder the terms:
-5 + 6p + -5p = -8 + -2(p + 12)

Combine like terms: 6p + -5p = 1p
-5 + 1p = -8 + -2(p + 12)

Reorder the terms:
-5 + 1p = -8 + -2(12 + p)
-5 + 1p = -8 + (12 * -2 + p * -2)
-5 + 1p = -8 + (-24 + -2p)

Combine like terms: -8 + -24 = -32
-5 + 1p = -32 + -2p

Solving
-5 + 1p = -32 + -2p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '2p' to each side of the equation.
-5 + 1p + 2p = -32 + -2p + 2p

Combine like terms: 1p + 2p = 3p
-5 + 3p = -32 + -2p + 2p

Combine like terms: -2p + 2p = 0
-5 + 3p = -32 + 0
-5 + 3p = -32

Add '5' to each side of the equation.
-5 + 5 + 3p = -32 + 5

Combine like terms: -5 + 5 = 0
0 + 3p = -32 + 5
3p = -32 + 5

Combine like terms: -32 + 5 = -27
3p = -27

Divide each side by '3'.
p = -9

Simplifying
p = -9`